Finite Element Analysis and Shape Optimization of Automotive Crash-Box Subjected to Low Velocity Impact - Li Qing-fen; Liu Yan-jie; Wang Hai-dou; Yan Sheng-yuan (2009 International Conference on Measuring Technology and Mechatronics Automation, 2009)
Crash-box equipped at the front end of a car, is one of the most important automotive parts for crash energy absorption. In case of frontal crash accident, it is expected to be collapsed with absorbing crash energy prior to other body parts so that the damage of the main cabin frame is minimized and passengers may be saved. In the present work, energy absorption characters of automobile crash-box at low-velocity impact are studied by using finite element method and shape optimization design for thin-walled tubes has been successfully proposed through choosing proper cross section and adopting appropriate grooves. Six types of thin-walled tubes with different cross section were studied and different grooves on the tubes were adopted and compared. Results show that the energy absorption characters improved obviously for square cross section thin-walled tube with double concave and bulgy grooves.